The obstacles and prospers of ecotourism behavior development in the visitors. An SLR from the literature reviewing from 2015-2019 - Imran, Amina; Siddique, Muhammad; Raza, Hamad; Khan, Nohman (The journal of contemporary issues in business and government, 2021)
In the past decades, tourism's impact on economics, social, culture, and society has increased. The concept of alternative tourism, such as nature-based travel, green travel, responsible travel, soft tourism, cultural tourism, adventure travel, and ecotourism, is growing very excessively as compared to ordinary tourism. The current study aims to determine the research direction on ecotourism behavior in the year 2015 to 2019. The 56 studies are included in the review from the Scopus database and following the PRISMA statement 2015. Classification of literature is divided into four significant categories after reviewing the literature and setting the inclusion and exclusion criteria. The most frequent theories also discussed, and theory of planned behavior used by the many researchers related to the ecotourism behavior. The findings showed that ecotourism behavior development research is focused on environmental protection. The behavioral development process is needed an ecotourism intention creating process. There is need to make efforts in multidisciplinary research.